Desarrollo de una metodología para el seguimiento y control de las actividades de extracción y colocación de materiales de préstamo en un tramo del proyecto Nueva Carretera a San Carlos - Rojas-Calderón, Andrey (Instituto Tecnológico de Costa Rica, 2012)
This work intends to develop an easy use and quick access control tool that allows users to link together variables affecting subgrade filling material activities and, from real equipment performance, it will be able to calculate the length based on the work volume, just as the required equipment; leaving choice to select the amount of machinery and workers involved. Also it looks forward to achieve an associated cost control, budgeting the cost of the activity for each section of the project and comparing it with the actually spent budget, to let users make the right decisions on time. All this based in data bases from Sánchez Carvajal Construction Company, this data bases can be modified according to the needs of the company. Besides, users can check equipment recommendations according to field observations and quality requirements according to regulations, all these in an easy and quickly way. Moreover this tool allows users to register all calculated information according to the sections of the project, its date and verified progress. Briefly, it is intended to develop a tool capable of linking important variables from the activity, in order to achieve a strict control, from the beginning to the end, with the opportunity of making choices when needed to keep the work as planned initially and registering all calculations related to these choices.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2012.
Keywords: Control de Costos; Préstamo Seleccionado; Proyecto Carretero